2015
DOI: 10.1039/c5cp00417a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of inverted polymer solar cells by introducing inorganic dopants

Abstract: Cadmium selenide (CdSe) quantum dots (QDs) utilized as additives have been incorporated intopolymer solar cells (PSCs) composed of poly[N-9''-hepta-decanyl-2,7-carbazolealt-5,5-(4',7'-di-2-thienyl-2',1',3'-ben-zothiadiazole)] (PCDTBT) and fullerene derivative [6,6]-phenyl-C71-butyric acid methyl ester (PC71BM). The maximum power conversion efficiency (PCE) of 6.94% has been achieved, corresponding to 33% enhancement compared with the control devices. The introduction of CdSe QDs allows not only the improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…PCDTBT and PC 71 BM were purchased from Lumtec Corp. Au AHNRs were synthesized by ourselves using anover-mediated growth reported previously. , TiO 2 solution was also prepared by ourselves according to some reported references. , MoO 3 and Ag were also purchased from Lumtec Corp.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…PCDTBT and PC 71 BM were purchased from Lumtec Corp. Au AHNRs were synthesized by ourselves using anover-mediated growth reported previously. , TiO 2 solution was also prepared by ourselves according to some reported references. , MoO 3 and Ag were also purchased from Lumtec Corp.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The addition of carbon allotropes into the active layer of a hybrid solar cell facilitates electron extraction and transfer. C 60 and C 70 fullerenes, with their high electron affinity, are very promising candidates as a third component for hybrid solar cells with QDs. To investigate the efficiency of such ternary blends for photovoltaics, we have performed steady-state and transient PL measurements of binary and ternary blends of P3HT, I-capped PbS QDs, and PCBM.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To conrm that PbS QDs gathers on the top of lms, 29,30 yield of lead ion, carbon ion and oxygen ion were measured respectively in the whole lm with doping 5% PbS QDs as shown in Fig. 4b.…”
Section: Resultsmentioning
confidence: 99%
“…Lee 23 et al introduced PbS QDs with different bandgap energy (0.9–1.7 eV) instead of [6,6]-phenyl-C 71 -butyric-acid methyl-ester (PC 71 MB) as an electron acceptor with poly[2,6-(4,40-bis(2-ethylhexyl)dithieno[3,2- b :20,30-d]silole)- alt -4,7(2,1,3-benzothiadiazole)] (PSBTBT) as the polymer donor, and got a PCE of 3.48%. Guo 24 et al reported a PCE of 6.94% by introducing the cadmium selenide (CdSe) QDs as an additive into the blend of poly [ N -900-hepta-decanyl-2,7-carbazole- alt -5,5-(40,70-di-2-thienyl-20,10,30-ben-zothiadiazole)] (PCDTBT) and the fullerene derivative PC 71 BM. The improvements of the photovoltaic performance were explained by improving the charge transport property and tuning the energy levels after introducing the QDs.…”
Section: Introductionmentioning
confidence: 99%